(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Climate change is a serious issue that not only affects Malaysia but also worldwide. Previous studies found that climate literacy may have a significant relationship with climate response while the level of education does not affect climate literacy. Thus, this study was conducted to gauge the level of climate literacy as well as their responses for Universiti Sains Malaysia (USM) students. A mobile climate application named SmaCli is proposed at the end of this study to address the issue of negative response towards climate change. The featuresof SmaCli are based on responses solicited from the questionnaire and the aim is to enhance climate literacy and encourage positive responses. However, for this paper, the prototype of the application is not included. A total of 196 responses were collected which consists of postgraduate and undergraduate students. The study found that 66% of the respondents have high literacy on climate change, level of education has no significant relationship with climate literacy level, mitigation act (climate response) showed a significant relationship with climate literacy level, and adaptation act (climate response) has no significant relationship with climate literacy. Hence, a concerted effort is still needed to improve climate literacy levels to ensure a positive climate response.